2008
DOI: 10.5641/193250308x13086753542852
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validation of Physical Activity Surveys in Culturally Diverse Older Adults: A Comparison of Four Commonly Used Questionnaires

Abstract: The purpose of this study was to establish validity evidence of four physical activity (PA) questionnaires in culturally diverse older adults by comparing self-report PA with performance-based physical function. Participants were 54 older adults who completed the Continuous Scale Physical Functional Performance 10-item Test (CS-PFP10), Physical Activity Scale for the Elderly (PASE), HAMPS Physical Activity Questionnaire for Older Adults, Yale Physical Activity Survey (YPAS), and modified Baecke questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The Yale Physical Activity Survey was administered to assess the subject's level of physical activity (Moore et al 2008) and the Fred Hutchinson Food Frequency Questionnaire was self-administered and estimates the frequency of food consumption and portion sizes (Michels and Willett 2009). …”
Section: Questionnairesmentioning
confidence: 99%
“…The Yale Physical Activity Survey was administered to assess the subject's level of physical activity (Moore et al 2008) and the Fred Hutchinson Food Frequency Questionnaire was self-administered and estimates the frequency of food consumption and portion sizes (Michels and Willett 2009). …”
Section: Questionnairesmentioning
confidence: 99%
“…Similarly, other studies have reported the existence of significant correlations between the estimated total amount of PA obtained from the questionnaire and the results gathered from performance-based physical function tests and self-reported physical functioning 10,31 . However, no correlation was found with the level of fitness when the Chair StandTest was employed, which contradicts previous observations in institutionalized populations 32 .…”
mentioning
confidence: 99%
“…Furthermore, the PASE has been correlated with direct measures of physical activity such as portable accelerometer and doubly labelled water, the gold standard for measuring physical activity [30,31]. Although designed originally for individuals older than 65 years, the PASE was validated previously in studies of younger participants [32,33]. The PASE has also been used to assess physical activity levels in several studies of younger samples [31,[34][35][36].…”
Section: Estimation Of Dietary Intake and Physical Activity Levelsmentioning
confidence: 99%